2012
DOI: 10.1016/j.vaccine.2012.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the 2010–2011 seasonal influenza vaccine in preventing confirmed influenza hospitalizations in adults: A case–case comparison, case-control study

Abstract: Influenza vaccination was associated with a significant reduction on the risk of confirmed influenza hospitalization, irrespective of age and high-risk conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 43 publications
0
32
0
Order By: Relevance
“…22,23 Recent Spanish observational studies found that vaccine effectiveness in preventing laboratory-confirmed influenza-related hospitalizations ranged from 31 to 59% in patients aged 65 y. [24][25][26] Influenza vaccination policy in most developed countries, therefore, targets people aged 65 y as part of the effort to reduce the burden of mortality and disability in this population.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Recent Spanish observational studies found that vaccine effectiveness in preventing laboratory-confirmed influenza-related hospitalizations ranged from 31 to 59% in patients aged 65 y. [24][25][26] Influenza vaccination policy in most developed countries, therefore, targets people aged 65 y as part of the effort to reduce the burden of mortality and disability in this population.…”
Section: Discussionmentioning
confidence: 99%
“…In studies evaluating Northern Hemisphere 2010–2011 IIV against influenza using primarily outpatient case and control patients, point estimates of VE among persons ≥60 years ranged from no significant effectiveness likely due to small sample sizes to approximately 70% effectiveness 8,11,12. In test-negative case–control studies evaluating the same vaccine strain composition against influenza-associated hospitalization in persons ≥60 years, point estimates ranged from 52% in a study using hospitalized case patients and outpatient control patients10 to 59% in a study using hospitalized control patients,9 consistent with our VE estimate.…”
Section: Discussionmentioning
confidence: 99%
“…Low vaccination uptake is a major challenge to using a test-negative case–control design to estimate influenza VE among target groups in countries with new influenza vaccination programs. Second, some case–control studies of IIV effectiveness define control patients as those who are negative for influenza viruses but positive for other respiratory viruses to control for respiratory specimen quality and reduce case misclassification due to false-negative influenza test results 9,16. Despite extensive testing for other respiratory viruses, we were unable to use this approach because there were too few patients with respiratory specimens negative for influenza but positive for other respiratory viruses.…”
Section: Discussionmentioning
confidence: 99%
“…There were some reports on the clinical effectiveness of the 2010-2011 influenza vaccine in a relatively small population of children (2)(3)(4)(5).…”
mentioning
confidence: 99%